USE OF GRAPHIC OBJECTS AT THE STUDY OFFOREIGN LANGUAGE (Pedagogy of Higher and Secondary Education, 2022)
The article investigates the problems of geographical objects and their usage while learning a foreign language. The author exemplifies the ways of using in class such geographical aids as maps, schemes, drawings, pictures, cartoon films. In particular the article proves the positive influence of graphical means of presentation on the development of students’ creative abilities while learning a foreign language.
Keywords: 1